Mortality due to circulatory diseases in women in the Northeast Region of Brazil from 2015 to 2020 – An Ecological Study (Research, Society and Development, 2022)
Introduction: In Brazil, diseases of the circulatory system emerge as the second leading cause of death affecting              women, and, especially in the Northeast region of Brazil, there has been an increase in mortality from these diseases, intensified by modifiable risk factors, such as stress. Objective: To describe the mortality from cardiovascular diseases in women in the northeastern region of Brazil between the years 2015 and 2020. Methodology: The data sources used were SIM, SIH/SUS, DATASUS and GBD, to define the epidemiological profile of cardiovascular disease mortality in women, inhabitants of the northeastern region in Brazil, between 2015 and 2020. Results and Discussion: The number of deaths from cardiovascular disease in the Northeast ranks second in Brazil, with 272,550 deaths per residence, second only to the Southeast. However, the region has the highest coverage of primary care. Among the Northeastern states, Bahia stands out with 64,227 deaths. Among the states in the Northeast, Bahia stands out with 64,227 deaths. Conclusion: It is noted that the Northeast occupies the second position regarding the number of deaths from cardiovascular diseases, mostly women, over 40 years, widows and mixed race.